Humanisasi dan Divinisasi dalam Seni dan Ritual - Heatubun, Fabianus Sebastian (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2016)
Metaphysically speaking, human being is a homo ritualis or a ritual being, and not simply because of the need for any ritual, but because of one’s ontological structure. At the same time, human is also a homo sapiens artisticus. One’s way of being and one’s mode of thinking is always artistic. One might also say that ritual is always artistic and art is always ritualistic. In this sense ritual and art are inseparable, for ritual and art are sui generis. Both exist in the area of human experience and are in touch with cognition, affection, knowledge, action, and enjoyment. Art and ritual are the hermeneutical site of meanings and values that simultaneously become the same place to find the answers. Imagined within the realness of life, art and ritual are a field of meanings. When human beings slip away from their humanity, art and ritual become the medium to restore it. Not only can art and ritual create a balance between the physical and the mental aspects, between the body and the soul that have been dehumanised, they also can exalt human beings towards the divine level as the culmination of the humanisation process.